Which fraction of stone wool fibre surface remains uncoated by binder? A detailed analysis by time-of-flight secondary ion mass spectrometry and X-ray photoelectron spectroscopy. Issue 62 (13th December 2021) - Hirth, Sabine; Waindok, Hubert; Wohlleben, Wendel
Abstract : ToF-SIMS mapping reveals that man-made vitreous fibres (MMVF) are fully covered with binder explaining variations in biodurability testing with simulated lung fluid described earlier. Abstract : Biodurability of man-made vitreous fibres (MMVF) is often measured on naked fibres, i.e. fibres devoid of the phenol-urea-formaldehyde (PUF) binder that is sprayed and baked on the commercial product to reduce dustiness and to provide mechanical strength to fibre mats. This simplification of the hazard assessment relies on the assumption that the binder would not actually coat the entire fibre surface, but would occur only at the touching points where two fibres are glued together. We challenged this assumption by using surface analysis by X-ray photoelectron spectroscopy (XPS) and Time-of-Flight Secondary Ion mass spectrometry (ToF-SIMS). We analysed commercial stone wool MMVF sourced from Denmark, United Kingdom and Germany. XPS as well as ToF-SIMS-mapping combined with gas-cluster-ion-sputtering revealed that all mineral fibres investigated show a complete layer of organics over the surface of the fibres with only a few defects: before sputtering, organic components (PUF binder and oils) uniformly cover the spatial structures; only after sputtering, the inorganic components of the stone wool emerge on the visible surfaces. A preferential localisation of PUF binder on fibre-to-fibre touching points or as droplets was not observable. We finally explored the correlation to dissolution rates, but found that total PUF binder content and the experimentally determined thickness of the PUF binder layer are not sufficient to predict dissolution rates, which instead must consider chemical composition and other properties. In summary, none of the investigated stone wool fibre surfaces were uncoated by the PUF binder.